Planowanie kosztów badań i rozwoju - Majerczyk, Halina (Research and Development Costs Planning, 2005)
There are a lot of methods of research and development costs planning. Depending on specificity of firm and research and development costs the best can be chosen. If research and development costs in amount to realize the aims in this sphere are planned, their level is made independent from the value of income or profit.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 284-290